Academic achievement in math and language of migrant and local students: The role of teachers’ educational expectations and ethnic composition - Ayala, M. Constanza (Education Policy Analysis Archives, 2022)
There is a vast literature in developed countries that has documented an ethnic gap in academic achievement, which favors local students. This evidence has discussed individual and structural factors. Despite this, there are still gaps that need to be addressed. This study seeks to deepen into the Latin American case and delve into the relationship between the educational expectations of teachers and the ethnic composition of the classrooms with the academic results of migrant and local students. Census data of fourth-grade students in Chile are used through standardized tests in mathematics and language and analyzed with multilevel models of four levels (students, classrooms, schools, and local authorities). The results suggest that children from ethnic minorities are at a disadvantaged compared to their national peers in mathematics, but not in language. The educational expectations of teachers have a positive relationship with academic achievement. The opposite happens with the percentage of migrant students in the classroom. Interaction analyses indicate that the association between teachers' educational expectations and academic achievement is moderated in part by the ethnic composition of the classroom. Finally, possible explanations for the observed findings and contributions to public policy are discussed.